Реалізація алгоритму відкривання дверей автономним мобільним роботом з використанням методів машинного навчання - Гладун , Ярослав Вікторович (Національний університет «Львівська політехніка», 2022)
Бакалаврська кваліфікаційна робота виконана студентом групи КН-409 Гладуном Ярославом Вікторовичом. Тема «Реалізація алгоритму відкривання дверей автономним мобільним роботом з використанням методів машинного навчання». Робота направлена на здобуття ступеня бакалавр за спеціальністю 122 «Комп’ютерні науки». Автономний мобільний робот (АМР) – це здатний до швидкого пересування робот, який спроможний виконувати певні завдання без регулярного людського нагляду. Для різних задач потрібен різний ступінь автономності. Високий ступінь автономності потрібен для таких задач, як прибирання будівлі, дослідження Марса, доставка їжі тощо. Для дуже широкого спектру задач важливо, щоб АМР міг виконувати притаманні людям дії у звичайних побутових умовах в приміщенні. Однією з таких дій є відкривання різного типу дверей. Це завдання важливе для будь-яких операцій, які включають в себе пересування роботом з однієї кімнати в іншу. Bachelor's qualification work was performed by a student of the KN-409 group Hladun Yaroslav Viktorovich. Topic "Implementation of the algorithm for door opening door by an autonomous mobile robot using machine learning methods." The work is aimed at obtaining a bachelor's degree in 122 "Computer Science". Autonomous Mobile Robot is a fast-moving robot capable of performing certain tasks without regular human supervision. Different tasks require different degrees of autonomy. A high degree of autonomy is required for tasks such as cleaning the building, exploring Mars, delivering food, and so on. For a very wide range of tasks, it is important that autonomous mobile robot be able to perform human activities in normal indoor conditions. One such action is to open different types of doors. This task is important for any operation that involves moving the robot from one room to another. In most cases, lidars (LIDAR transliteration: Light Identification, Detection and Ranging) are used to localize the robot in the building. Typically, leader data is fed to either the Particle Filter (PF) algorithm or the Kalman Filter (KF) algorithm. The problem with inexpensive lidars is that they are not accurate enough to allow the robot hand to hit the door handle, as an error of only 2-3 centimeters can cause the endefector to miss, and therefore the door can not be opened. So we can conclude that in this task you need to use machine learning algorithms, as most autonomous mobile robot for such operations, of the sensors that allow you to see the doorknob have only a camera, so it becomes relevant direction of object recognition in the image from the camera in this task. That is, you need to constantly adjust the position of the door handle relative to the endefector to get on it and successfully open the door.
Implementation of the algorithm for door opening door by an autonomous mobile robot using machine learning methods
Keywords: Door Handle Detection, Robotics Door Operation, Real Time Object Detection, RGBD Stereo Camera, Kinematic Model Learning, Robotic Arm